Robust, universal biomarker assay to detect senescent cells in biological specimens. Issue 1 (17th November 2016) - Evangelou, Konstantinos; Lougiakis, Nikolaos; Rizou, Sophia V.; Kotsinas, Athanassios; Kletsas, Dimitris; Muñoz‐Espín, Daniel; Kastrinakis, Nikolaos G; Pouli, Nicole; Marakos, Panagiotis; Townsend, Paul; Serrano, Manuel; Bartek, Jiri; et al.
Summary: Cellular senescence contributes to organismal development, aging, and diverse pathologies, yet available assays to detect senescent cells remain unsatisfactory. Here, we designed and synthesized a lipophilic, biotin‐linked Sudan Black B (SBB) analogue suitable for sensitive and specific, antibody‐enhanced detection of lipofuscin‐containing senescent cells in any biological material. This new hybrid histo‐/immunochemical method is easy to perform, reliable, and universally applicable to assess senescence in biomedicine, from cancer research to gerontology.